2020
DOI: 10.7150/thno.44370
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Astrocyte-Neuron Lactate Shuttle System contributes to Neuroprotective action of Fibroblast Growth Factor 21

Abstract: A viewpoint considering Alzheimer's disease (AD) as “type 3 diabetes” emphasizes the pivotal role of dysfunctional brain energy metabolism in AD. The hormone fibroblast growth factor 21 (FGF21) is a crucial regulator in energy metabolism; however, our understanding of the therapeutic potential and mechanisms underlying the effect of FGF21 on neurodegeneration of AD is far from complete. Methods: To further elucidate the effect of FGF21 on AD-related neurodegeneration, we used APP/PS1 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 74 publications
2
30
0
Order By: Relevance
“…We turned our attention to the genes that were significantly up-regulated only in WT astrocytes and generated a full list of the 209 genes ( Supplementary File 1 ). The first two genes in this category were fibroblast growth factor 21 (Fgf21), which encodes a growth factor with neuroprotective effects ( 29 ), and interleukin 11 (Il-11), which encodes a member of the IL-6 family of cytokines with a potential role in driving astrocyte differentiation through the activation of STAT3 ( 30 ). RGC-32 itself was the 14 th most up-regulated gene (Rgcc), a result that was not surprising because TGF-β is a potent inductor of its expression ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…We turned our attention to the genes that were significantly up-regulated only in WT astrocytes and generated a full list of the 209 genes ( Supplementary File 1 ). The first two genes in this category were fibroblast growth factor 21 (Fgf21), which encodes a growth factor with neuroprotective effects ( 29 ), and interleukin 11 (Il-11), which encodes a member of the IL-6 family of cytokines with a potential role in driving astrocyte differentiation through the activation of STAT3 ( 30 ). RGC-32 itself was the 14 th most up-regulated gene (Rgcc), a result that was not surprising because TGF-β is a potent inductor of its expression ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, FGF21 induced by calorie restriction reduced tau phosphorylation through the mTOR axis, and tau pathology was ameliorated by FGF21 in Aβ-treated SH-SY5Y cells [205,207]. Furthermore, astrocyteneuron lactate shuttle (ANLS) was implicated in decreased tau phosphorylation by FGF21 in a transwell co-culture system with C6 astrocytes and PC12 neurons [208].…”
Section: Aβ Production and Tau Phosphorylationmentioning
confidence: 96%
“…Although not many studies have been conducted on the effect of FGF21 on NDs, several recent preclinical studies have shown that FGF21 has a neuroprotective effect in ND models by affecting several signaling pathways. In both in vivo and in vitro AD models, FGF21 has shown anti-inflammatory and antioxidant effects, and prevented amyloid plaque formation, neurofibrillary tangle formation, and neurodegeneration [205][206][207][208]. Moreover, FGF21 treatment led to alleviated dopaminergic neuron loss, improved mitochondrial function and behavioral ability, and decreased inflammation in PD models [209][210][211][212].…”
Section: Fgf21mentioning
confidence: 99%
“…FGFs, such as FGF-2 and FGF-21, have been shown to be beneficial to treat AD hallmarks ( Table 1 ) [ 112 , 219 ]. While no difference was detected in the levels of LMW FGF-2 between AD patients and age-matched healthy controls, the expression of HMW FGF-2 isoforms was drastically decreased in AD patients [ 219 ].…”
Section: Growth Factors In Brain Function and Admentioning
confidence: 99%